Development of naringenin-O-carbamate derivatives as multi-target-directed liagnds for the treatment of Alzheimer's disease. (15th March 2022) - Mi, Jing; He, Ying; Yang, Jing; Zhou, Yi; Zhu, Gaofeng; Wu, Anguo; Liu, Wenmin; Sang, Zhipei
Graphical abstract: Highlights: 3c was a good and balanced multifunctional agent. 3c was a good antioxidant agent and selective metal ions chelator. 3c presented good neuroprotective effect and hepatoprotective effect. 3c demonstrated favourable BBB penetration in vitro and drug-like property. Abstract: In this work, a series of naringenin- O -carbamate derivatives was designed and synthesized as multifunctional agents for the treatment of Alzheimer's disease (AD) through multi-target-directed ligands (MTDLs) strategy. The biological activity in vitro showed that compound 3c showed good antioxidant potency (ORAC = 1.0 eq), and it was a reversible hu AChE (IC50  = 9.7 μM) inhibitor. In addition, compound 3c significantly inhibited self-induced A β 1-42 aggregation, and it could activate UPS degradation pathway in HT22 cells and clear the aggregated proteins associated with AD. Moreover, compound 3c was a selective metal chelator, and it significantly inhibited and disaggregated Cu 2+ -mediated A β 1-42 aggregation. Furthermore, compound 3c displayed remarkable neuroprotective effect and anti-inflammatory property. Interestingly, compound 3c displayed good hepatoprotective effect by its antioxidant activity. More importantly, compound 3c demonstrated favourable blood–brain barrier penetration in vitro and drug-like property. Therefore, compound 3c was a promising multifunctional agent for the treatment of AD.